2023
DOI: 10.3390/app132011484
|View full text |Cite
|
Sign up to set email alerts
|

The Detection of Bacterial Pathogens, including Emerging Klebsiella pneumoniae, Associated with Mastitis in the Milk of Ruminant Species

Efstathia Tsakali,
Andreas G. Tsantes,
Dimitra Houhoula
et al.

Abstract: Milk is an excellent medium for the growth of several bacteria and other microorganisms and thus, it has been extensively studied. An always current issue in the dairy industry is mastitis, which causes losses in milk volume and profits. In many cases, milk is used raw or treated at low temperatures for further dairy processes while there are quite a few cases in which foodborne-related outbreaks have occurred. Both culture-based methods and PCR were used to assess the presence of certain pathogens related to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…Several studies in Nigeria reported drug-resistant Klebsiella strains in raw animal milk and milk products; however, genomic data and serotypes of the reported strains are rare [13,14]. Molecular characterization of the resistance factors associated with strain Cow102 revealed the presence of 38 Antibiotic Resistance Genes (ARGs) (Table 1 and Fig.…”
Section: Antimicrobial Resistance Genesmentioning
confidence: 99%
“…Several studies in Nigeria reported drug-resistant Klebsiella strains in raw animal milk and milk products; however, genomic data and serotypes of the reported strains are rare [13,14]. Molecular characterization of the resistance factors associated with strain Cow102 revealed the presence of 38 Antibiotic Resistance Genes (ARGs) (Table 1 and Fig.…”
Section: Antimicrobial Resistance Genesmentioning
confidence: 99%